Surface vs. deep acting in EFL instruction: mediating and moderating roles of emotion regulation and intelligence in burnout - Zhang, Feng (Frontiers in Psychology, 2025)
IntroductionTeaching English as a Foreign Language (EFL) is a profession characterized by high cognitive and emotional demands, leading to persistent challenges with teacher burnout (TB). While emotion regulation (ER) is known to protect against burnout, this study investigates the distinct roles of emotional labor strategies—surface acting and deep acting—within high-pressure academic cultures. It further examines whether ER mediates the relationship between surface acting and burnout, and if emotional intelligence (EI) moderates this pathway by buffering the negative effects of surface acting.MethodsA cross-sectional survey was administered to 448 EFL instructors in China, yielding a recovery rate of 93.08%. We employed structural equation modeling (SEM) to test five hypotheses, conducting mediation analysis to assess the role of ER and moderation analysis to evaluate the protective effect of EI.ResultsThe results confirmed that frequent use of surface acting was positively associated with higher levels of TB, whereas deep acting was linked to lower burnout. ER functioned as a significant mediator, partially explaining the detrimental impact of surface acting on burnout. Furthermore, emotional intelligence served as a significant moderator; instructors with higher EI were less affected by the negative consequences of surface acting on their wellbeing.DiscussionThese findings underscore the critical distinction between dysfunctional (surface acting) and functional (deep acting) emotional labor strategies in EFL contexts. The study promotes deep acting as a more sustainable ER strategy and highlights the protective role of EI. Consequently, targeted training programs designed to enhance ER skills and develop EI are recommended as effective interventions to safeguard the wellbeing of EFL instructors operating in high-stress academic environments.